Globalization in the Time of COVID-19 - Alessandro Sforza; Marina Steininger (Center for Economic Studies and ifo Institute (CESifo), 2020)
The economic effects of a pandemic crucially depend on the extend to which countries are connected in global production networks. In this paper we incorporate production barriers induced by COVID-19 shock into a Ricardian model with sectoral linkages, trade in intermediate goods and sectoral heterogeneity in production. We use our model to quantify the welfare effect of the disruption in production that started in China and then quickly spread across the world. We find that the COVID-19 shock has a considerable impact on most economies in the world, especially when a share of the labor force is quarantined. Moreover, we show that global production linkages have a clear role in magnifying the effect of the production shock. Finally, the economic effects of the COVID-19 shock are heterogeneous across sectors, regions and countries, depending on the geographic distribution of industries in each region and country and their degree of integration in the global production network.
Keywords: F10; F11; F14; F60; 330; COVID-19 shock; globalization; production barrier; sectoral interrelations; computational general equilibrium